Systemic delivery of adeno-associated viral vectors - Duan, Dongsheng (Curr Opin Virol, 2016)
For diseases like muscular dystrophy, an effective gene therapy requires bodywide correction. Systemic viral vector delivery has been attempted since early 90s. Yet a true success was not achieved until mid-2000 when adeno-associated virus (AAV) serotype-6, 8 and 9 were found to result in global muscle transduction in rodents following intravenous injection. The simplicity of the technique immediately attracts attention. Marvelous whole body amelioration has been achieved in rodent models of many diseases. Scale-up in large mammals also shows promising results. Importantly, the first systemic AAV-9 therapy was initiated in patients in April 2014. Recent studies have now begun to reveal molecular underpinnings of systemic AAV delivery and to engineer new AAV capsids with superior properties for systemic gene therapy.